Effectiveness of metoclopramide in preventing the incidence of post-operative nausea and vomiting in lower-segment caesarean section - ., Rashmi; PT, Shivanand; ML, Manjunath (International Journal of Research in Medical Sciences, 2017)
Background:The common and distressing symptoms which follow anaesthesia and surgery are pain, nausea and vomiting. Nausea and vomiting are the most common side effects in the post- anaesthesia care unit. But post-operative nausea and vomiting have received less attention, though there are extensive literature, data are frequently difficult to interpret and compare. Therefore, the present study was undertaken to investigate the efficacy and safety of IV Metoclopramide as prophylaxis for postoperative nausea and vomiting in lower-segment caesarean section (LSCS) under spinal anaesthesia. Methods: After institutional approval and informed consent fifty ASA I and II patients undergoing non-emergent LSCS taken for study. The patients received IV Metoclopramide 10 mg. Anaesthetic management was standardized. The incidence of vomiting and retching as number of episodes was studied. Nausea was graded depending on the severity and data derived. Results: The mean episodes of emesis, nausea and retching at different postoperative duration were recorded. 64% patients experienced emesis at 1 hour. The incidence of nausea was more (56%) at 1 hour. 52 % of patients experienced retching at 1 hour whereas, 64% at 2 hour of postoperative. Conclusions: Injection of Metoclopramide (10 mg) decreased the incidence of PONV as the side effect with this drug was minimal.